2008
DOI: 10.3390/s8095426
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Effects on InSAR Measurements and Their Mitigation

Abstract: Interferometric Synthetic Aperture Radar (InSAR) is a powerful technology for observing the Earth surface, especially for mapping the Earth's topography and deformations. InSAR measurements are however often significantly affected by the atmosphere as the radar signals propagate through the atmosphere whose state varies both in space and in time. Great efforts have been made in recent years to better understand the properties of the atmospheric effects and to develop methods for mitigating the effects. This pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
97
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(98 citation statements)
references
References 69 publications
0
97
0
1
Order By: Relevance
“…The aforementioned geological features, along with the historical landslide in the Hope Slide, draws attention to using the TSX-ST images to perform a comprehensive analysis of slope stability on and around Hope Slide, to better understand the triggers and dynamics of mass movements in the area. Due to the topography of the area, the Hope Slide is exposed to strong turbulent mixing processes, atmospheric stratification, and changes in atmospheric pressure in time, which introduce significant atmospheric errors to these high resolution TSX-ST images [12]. Addressing and modelling the atmospheric effect (e.g., by means of the methodology described in Sections 3.1 and 3.2) plays a key role in retrieving the deformation phase from the TSX-ST acquisitions for the Hope Slide.…”
Section: Data and Test Sitesmentioning
confidence: 99%
“…The aforementioned geological features, along with the historical landslide in the Hope Slide, draws attention to using the TSX-ST images to perform a comprehensive analysis of slope stability on and around Hope Slide, to better understand the triggers and dynamics of mass movements in the area. Due to the topography of the area, the Hope Slide is exposed to strong turbulent mixing processes, atmospheric stratification, and changes in atmospheric pressure in time, which introduce significant atmospheric errors to these high resolution TSX-ST images [12]. Addressing and modelling the atmospheric effect (e.g., by means of the methodology described in Sections 3.1 and 3.2) plays a key role in retrieving the deformation phase from the TSX-ST acquisitions for the Hope Slide.…”
Section: Data and Test Sitesmentioning
confidence: 99%
“…If microwave pulses pass through locally dense vapor in the troposphere, there appears a time delay caused by the vapor, and the path difference becomes ∆R + ∆R T where ∆R T is the path difference corresponding to this time delay [610,611]. The path difference ∆R T may be as large as tens of centimeters in spatial scale [608], and therefore, the interferometric phase corresponding to this delay causes erroneous measurements of surface topography or deformation [612,613]. It is common to separate the tropospheric delays into two components: one related to turbulent mixing processes and the other related to tropospheric stratification.…”
Section: Atmospheric and Ionospheric Effectsmentioning
confidence: 99%
“…It was also suggested that the removal of the atmospheric effects before phase unwrapping reduces the errors in phase unwrapping in the areas of high relief [628]. For further details, see a good review article on the issue of atmospheric effects and their mitigation [612,613].…”
Section: Atmospheric and Ionospheric Effectsmentioning
confidence: 99%
“…The InSAR technique has excellent ability to reveal spatial pattern of the subsidence in more detail. However, InSAR technique is inevitably affected by spatiotemporal decorrelation [7] and atmospheric delay [8], which significantly reduce the accuracy of InSAR measurements. To overcome such drawbacks, Ferretti et al proposed the persistent scatterer interferometry (PSI) method in 2001 [9].…”
Section: Introductionmentioning
confidence: 99%